Definition and Measure of the Sound Quality of the Machine - PLEBAN, Dariusz (Archives of Acoustics, 2014)
The analysis of available literature indicates that tests of products sound quality, which would not involve participation of groups of listeners supposed to evaluate the sounds emitted by these products, are neither carried out in Poland, nor in the world. That results in the fact that the products sound quality is determined on the basis of psychoacoustic information and comprises both objective and subjective factors of sound perception. With reference to those factors and to different life cycles of the machine, an original definition of the “sound quality of the machine” has been developed and presented in this article. The global index of the acoustic quality of the machine, accounting for the relations between the noise level at the workstation and the selected parameters characterising both the machine’s sound activity and the working environment, was adopted as the measure of the sound quality of the machine. The experiments that followed confirmed the appropriateness of the assessment made with the use of the global index of acoustic quality.